Security in Wireless Sensor Network: A Survey (International Journal of Communication Systems and Network Technologies, 2015)
Wireless Sensor Network (WSN) is gaining importance in modern application. WSNs are used to gather information in the form of images, signals, audios etc. remotely. The gathered information is sent to the receivers using special transducers. They are beneficial in many fields such as military purposes, wind speed calculation, for sensing forest fires etc. The main components of WSN are aggregation and Base System. Aggregation gathers data from the nearby environment, filters it and sends it to the Base System. However WSN are often limited in terms of memory and power and thus making it vulnerable to various security threats. In this paper, we focus on various WSN constraints and kinds of threat WSN faces.
Keywords: WSN; Security; Attacks